Massive change - Mau, Bruce, 1959-; Leonard, Jennifer, ....- (London : Phaidon, 2005)
Introduction : now that we can do anything, what will we do? Urban economies (URB) Movement economies (MOV) Energy economies (ENE) Information economies (INF) Image economies (IMA) Market economies (MAR) Material economies (MAT) Military economies (MIL) Manufacturing economies (MAN) Living economies (LIV) Wealth and politics (WP)
Keywords: Duurzame ontwikkeling; Ontwerpen